'Now she prefers jeans, like everyone else…' – Parents' experiences of group‐ and web‐based treatment of children's obesity. (15th February 2021) - Thorén, Annelie; Janson, Annika; Persson, Margareta
Abstract: Aim: Web‐based interventions have shown promising results in paediatric obesity treatment with the potential to increase coverage of care. This study aimed to explore parental experiences about participating in an intervention to improve healthy behaviours and lower BMI‐SDS in children with obesity. Methods: This was an interview study with an inductive qualitative approach. Data were collected from individual interviews with 14 parents of 5‐ to 13‐year‐old children with obesity. The respondents had participated in a family‐based treatment intervention consisting of four group sessions followed by 12‐week web‐based support. The interviews were analysed using qualitative manifest and latent content. Results: The overarching theme 'A transformative journey of lifestyle changes for the whole family' described how the participation impacted the lifestyle of the whole family. Four categories: parental awareness, introducing new routines, negotiating family battles and a feeling of support, represented various experiences made by respondents. The parents shared predominantly positive experiences of the intervention but also expressed feelings of guilt and struggled to address their child's obesity. Conclusion: Parents who participated in a study for children with obesity with a web‐based component found the programme helpful for achieving healthier lifestyles for the whole family.